Squamous odontogenic tumor: literature review focusing on the radiographic features and differential diagnosis - Mardones, Nilson do Rosário; Gamba, Thiago de Oliveira; Flores, Isadora Luana; Almeida, Solange Maria de; Lopes, Sérgio Lúcio Pereira de Castro [UNESP] (Bentham Open, 2015)
Since its first publication in 1975, the squamous odontogenic tumor remains the rarest odontogenic lesion, with around 50 cases in the English-language literature in which the microscopic characteristics are frequently very well demonstrated. However, articles which discuss the radiographic aspects are scarce, especially with emphasis on the differential diagnosis. The present treatise proposes an assessment of jaw lesions with the same radiographic characteristics of the squamous odontogenic tumor to clarify the main findings for dental clinicians during routine diagnosis.
Keywords: Differential diagnosis; Non-odontogenic lesions; Odontogenic lesions; Radiographic aspects; Squamous odontogenic tumor